2023
DOI: 10.1021/acs.chemmater.3c00346
|View full text |Cite
|
Sign up to set email alerts
|

Smart Design of Noble Metal–Copper Chalcogenide Dual Plasmonic Heteronanoarchitectures for Emerging Applications: Progress and Prospects

Abstract: Dual plasmonic metal–semiconductor heteronanostructures have been actively investigated due to their outstanding functional characteristics arising from the merging of two materials. In this review, the synthetic approaches, various designs, enhanced properties, and prospective applications of noble metal–nonstoichiometric copper chalcogenide nanosystems are summarized. The tunable size, shape, structure type (solid or hollow), composition, and doping level of the constituents produce several configurations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…Inhibitor assay and specificity test further confirmed the critical role of M pro in the dissociation process, showing no non-specific activation. Our dissociation peptides successfully dissociated silver clusters, demonstrating the capability of our dissociation platform for potential future studies involving a variety of plasmonic nanomaterials including anisotropic or multicomponent nanostructures that can induce distinct changes in extinction spectra through the dissociation process. Lastly, we demonstrated that our dissociation strategy can be less interrupted by matrixes such as human plasma, urine, and seawater, and the dissociated AuNPs maintained high colloidal stability.…”
Section: Discussionmentioning
confidence: 87%
“…Inhibitor assay and specificity test further confirmed the critical role of M pro in the dissociation process, showing no non-specific activation. Our dissociation peptides successfully dissociated silver clusters, demonstrating the capability of our dissociation platform for potential future studies involving a variety of plasmonic nanomaterials including anisotropic or multicomponent nanostructures that can induce distinct changes in extinction spectra through the dissociation process. Lastly, we demonstrated that our dissociation strategy can be less interrupted by matrixes such as human plasma, urine, and seawater, and the dissociated AuNPs maintained high colloidal stability.…”
Section: Discussionmentioning
confidence: 87%
“…In case of a halide perovskite, the facets of orthorhombic CsPbBr 3 , the most widely studied halide perovskite nanocrystals, are considered to provide the driving force for connecting chalcogenide nanostructures. ,, At the beginning, a six-faceted cube shape was reported ,, and then tuning ligand chemistry, 12 as well as 26 faceted nanocrystals which have different exposed surfaces are synthesized. These polyhedral nanocrystals indeed opened an avenue in providing more opportunities for possible lattice matching induced heteroepitaxy formation. However, these are limited and no generic route or the reaction chemistry is established yet which could guide the formation of larger combinations of heterostructures for perovskite family like the widely established chalcogenide or metal oxide systems. …”
Section: Introductionmentioning
confidence: 99%
“…The creation of a heterojunction between plasmonic metals and semiconductors is a promising strategy for tuning optical responses and tailoring properties in photo- and electrochemical catalysis. Hybrid nanostructures consisting of a plasmonic Au metal core and a Cu 2– x Se semiconductor shell are known as dual-plasmonic hybrid nanomaterials. At the interface between plasmonic metal and semiconductor within core@shell-structured Au@Cu 2– x Se nanoparticles, an Ohmic junction is formed between Au and Cu 2– x Se owing to the comparatively lower work function of the p-type semiconductor (Φ Cu 2– x Se = 4.8 eV) compared to that of metal Au (Φ Au ∼ 5.2–5.4 eV) (Φ s < Φ M ). , As a result, electrons are spontaneously transferred from Cu 2– x Se to Au through the heterointerface until the Fermi levels reach equilibrium, creating a strong interfacial electrical field in the heterostructure. This interfacial electric field induces electron depletion on the surface of Au@Cu 2– x Se nanoparticles. , This can be used to facilitate N 2 adsorption while preventing H + adsorption, thus enhancing the ENRR performance.…”
Section: Introductionmentioning
confidence: 99%